Evaluation of market with accommodation facilities considering risk influence: Case study Slovakia - Adriana Csikosova; Katarina Culkova; Erik Weiss; Maria Janoskova (Journal of Risk and Financial Management, 2021)
Tourism currently contributes significantly to the national economy. When investing in the accommodation facility on the real-estate market, the tourism sector also represents a certain risk due to a high level of seasonality. This paper investigates the risks related to prices, income and occupancy of accommodation facilities for selected regions in Slovakia. The value of accommodation facilities is estimated using discounted cash flow, probabilistic distribution of rental prices and occupancy of accommodation facilities in selected Slovak regions. The results provide information for potential and profitable investments in exposed regions in tourism. The information can be used in the field of risk management to avoid or reduce the risk of risk investments. Although the resulting values were calculated only for some selected regions, the proposed procedure can be used for any region and compared with the current values.
Keywords: 330; accommodation facilities; discounted cash flow; occupancy of the tourism locality; risk investments; Slovakia; tourism